ARDUINO-BASED DIGITAL DOOR LOCK SYSTEM WITH BLUETOOTH CONNECTIVITY (International Journal of Food and Nutritional Sciences, 2021)
Providing security is the project's main goal. These days, every company needs a security system. One technology that is utilised for security in many organisations is the access control system. This project's primary goal is to restrict access to authorised users alone and grant it only in the event that a given user's password matches. For security reasons, these doors with secret code locking mechanisms are very helpful. Numerous departments, including the Department of Defence, military zones, Research and Development, bank security, and protection for critical documents This kind can be used by industries, godowns, etc. when a high degree of security is required. The primary benefit of this method, which is applicable even domestically, is that only individuals with permission can open these doors. This system is intelligent enough to only accept legitimate passwords. The operator is presented with a four-digit code as a password; if the code is typed correctly using the Bluetooth keyboard, the door will open immediately. A message is sent over Bluetooth to the authorised mobile device and a buzzer is sounded if the password is entered incorrectly. It also features a mechanism with push buttons that allows the user to input the right pattern. If the password is entered correctly, the door will open; if not, a message will be sent to the device that is within range of the Bluetooth module (HC05), and the buzzer will sound.